Analysis Algorithm and Factors of International Economic Activity in The Coordinate System of Enterprises' Organizational Development - Sviatoslav KNIAZ; Nellі HEORHIADI; Lyubomyr SOPILNYK; Iryna KONOVALYUK; Yuriy TYRKALO; Ruslan SKRYNKOVSKYY; Svitlana MOROZ; Olena KALASHNYK; Mariana KHMYZ; Khrystyna KAYDROVYCH (Communications of International Proceedings, 2021)
The paper identifies the essential characteristics of international economic activity and highlights the factors that need to be taken into account in its implementation. This made it possible to clarify the place of international economic activity in the coordinate system of organizational development and prove that international economic activity can be carried out at the interstate, regional and global levels. The subject of international economic activity determines the subjects that carry it out. The relationship between the subject and subjects of international economic activity significantly depends on the economic system of a particular state.
Keywords: international economic activity; foreign economic activity; factors; organizational development; regulation.